2017
DOI: 10.3389/fnins.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Cognitive Functions, Plasma DNA, and White Matter Integrity in Patients with Early-Onset Parkinson's Disease

Abstract: Early-onset Parkinson's disease (EOPD) patients are symptomatic at a relatively young age, and the impacts of the disease on both the patients and their caregivers are dramatic. Few studies have reported on the cognitive impairments seen in EOPD, and the results of these studies have been diverse. Furthermore, it is still unclear what microstructural white matter (WM) changes are present in EOPD patients. As such, we conducted this study to investigate the microstructural WM changes experienced by EOPD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…-Low FA of primarily the frontal and parietal regions correlated with executive, visuospatial dysfunctions (20)(21)(22)(23)(24).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 98%
“…-Low FA of primarily the frontal and parietal regions correlated with executive, visuospatial dysfunctions (20)(21)(22)(23)(24).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 98%
“…The association between WM damages and systemic inflammation was demonstrated in current and previous studies [50, 51]. The result of linear regression analysis, controlling confounding effects, emphasized the major impacts of systemic inflammation including granulocyte apoptosis, lymphocyte apoptosis, LFA-1, and P-selectin.…”
Section: Discussionmentioning
confidence: 59%
“…Increased apoptosis of lymphocytes and monocytes and increased expression of LFA-1 might support the view that there is only one primary pathophysiology of PD: abnormal systemic oxidative stress and the acceleration of peripheral immune cell infiltration into the brain. Neurodegeneration in PD associated with systemic inflammation via various pathways has been thoroughly discussed [ 12 , 13 , 16 18 , 24 , 25 ]. Several previous studies showed that higher percentages of peripheral apoptotic lymphocytes [ 32 ] and the CNS infiltration of lymphocytes and monocytes contribute to neurodegeneration [ 22 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This association has been further been demonstrated by the increased peripheral leukocyte apoptosis with striatal dopamine neuron loss [ 16 ] and white matter alteration observed through the use of diffusion tensor imaging [ 17 ]. In addition, increased oxidative stress has been found to be associated with cognitive function status even in the early stage of the disease in young PD patients [ 18 ]. The accumulating evidence has shown an association between inflammation and cognitive impairment not only in PD [ 19 ] but also in other neurodegenerative diseases such as AD [ 20 ] and even in changes due to normal aging [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation